IMPLEMENTACIÓN DE UN SISTEMA CONTABLE EN EL COMERCIAL “COVIHOGAR” DE LA CIUDAD DE LOJA, PERÍODO ENERO - MARZO DE 2014 - Soto Vinces, Lizbeth Carolina (2016)
This thesis called "IMPLEMENTATION OF AN ACCOUNTING SYSTEM IN THE COMMERCIAL" COVIHOGAR "LOJA CITY, PERIOD JANUARY - MARCH 2014" was conducted in compliance with the general aim, and to provide a tool which will allow the owner better decision making in their activities and be able to take proper control of its operations. Also it was possible to meet the specific objectives were posed: An inventory to ensure adequate enforcement of existing goods, which would make through physical verification of the goods in stock; Implement the method for valuing inventories, the development of this objective the perpetual inventory system was applied by using cards with transcript valuation method "weighted average"; Another objective is to establish a specific plan of accounts and according to the needs of business, this lens was developed according to the needs and obligations arising in the course of daily business activities. and it was based the one chart of accounts. For the implementation of this practice based on the methodological aspect is deductive application, being a highly technical career but for the development of the accounting process was supported in auxiliary methods such as: scientific, inductive, analytical, systematic and mathematical basis from the previous business visit to the observation of the existing merchandise, then we collect the information source January to March 2014 provided by the owner which was 5 revised, classify and analyze information that helped us to realize the initial inventory allowing me to know the real value of assets liabilities $ 26,956.55 $ 71,628.14 $ 44,671.59 capital and bringing the accounting process starting from the initial inventory began to conclude with the preparation of financial statements which yielded a Net income of $ Activity Liquidity, Debt and Profitability: 2138.66, then indicators was applied. It also allowed us to summarize the theoretical process by selecting the most important and essential. The investigation and obtaining the results was possible to determine the conclusions and recommendations. In concluding that the commercial does not keep records of purchase and sale, or control of the goods, the owner is recommended to wear permanently Accounting and obtain real states, also apply indicators at least twice a year to get information liquidity, performance and indebtedness for proper decision making.